The Issues of Stress and its Reduction Methods in Modern Science - Stella , Pak; Kanyshay , Kojogeldieva; Saadat , Imankulova (Journal of Ecohumanism, 2025)
In everyday life, the word "stress" is often used as a synonym for strong excitement, emotions. But this concept is much broader. Stress is the body’s reaction to any irritating effects: problems at work, exams, hunger, lack of sleep, even fluctuations in atmospheric pressure. For many people, such stresses interfere with normal psychological, physical and social functioning. Prolonged stress damages the mechanisms of self-regulation of the body and leads to subsequent disturbances of biorhythms. The natural cycle of sleep and wakefulness changes, as a result, performance and self-control decrease, memory and attention deteriorate. Daily fluctuations in hormone levels, breathing rhythms and heartbeat are also disrupted. Chronic stress weakens the immune system, suppresses the protective reactions and barrier functions of the cells of the gastrointestinal tract and skin, which complicates the course and prognosis of any somatic diseases, including infectious. As a result, stress increases the risk of so-called "diseases of civilization" and contributes to their development: hypertension, diabetes mellitus, bronchial asthma, chronic pain, immune disorders and many others